Religiosity as a Moderator in the Relationship between Business Ethics and Sustainable Business Practices with Consumer Perceptions of Creative MSMEs - Setiawan, Temy; Bwarleling, Theresia Hesti; Bimo, Irenius Dwinanto (Universitas Brawijaya, Indonesia, 2025)
Business ethics and sustainable business practices are important factors in building consumer trust and loyalty, especially in the context of sustainability and social responsibility. Religiosity is considered a moderating factor because the moral and ethical values held by consumers can influence their evaluation of a business. This study aims to analyze the influence of business ethics and sustainable business practices on consumer perceptions of Micro, Small, and Medium Enterprises (MSMEs) in the creative sector, with religiosity as a moderating variable. This study employs a quantitative approach, focusing on the population of consumers of MSMEs in the Creative Sector of Cimahi City, with a sample of 150 individuals whose data were collected through questionnaires. Path analysis techniques are used to evaluate direct and indirect relationships between variables. The results of the study indicate that business ethics and sustainable business practices influence consumer perceptions, where MSMEs in the creative sector in Cimahi City can apply ethical and sustainable principles to improve their business trust and image. In addition, the variable of religiosity plays a significant role in moderating the relationship between business ethics and sustainable business practices on consumer perceptions, indicating that religious values can enhance the impact of the business strategy implemented.